FORMS OF MANIFESTATION OF THE KHUFYONA ECONOMY IN UZBEKISTAN AND ITS FIGHT AGAINST IT - Nizametdinov, Ali; Kholikov, Dilshad (Science technology&Digital finance, 2023)
Today, there is a wide range of opportunities for comprehensive support of entrepreneurs. Bringing these efforts to the population, in particular to businessmen, ending the problems that plague them is one of the main tasks of tax authorities, among a number of ministries and departments.